The Term 'Marketing' in the Islamic Jurisprudential Heritage and Its Impact on Controlling the Legality of Marketing Practices - عمار مايا (Journal of King Abdulaziz University: Islamic Economics, 2024)
This study explores the concept of marketing within the context of Islamic jurisprudential heritage and its influence on establishing the legality of marketing practices. Existing studies on Islamic marketing usually combine the term "marketing" with either Islam or the guidelines and regulations of Islamic jurisprudence. They generally aim to discern whether Islamic marketing exists as an independent discipline with its unique foundations and principles distinct from traditional marketing or if it merely applies Islamic legal rulings to traditional marketing topics. Some studies also present the Islamic perspective on contemporary marketing sciences. Regardless of the stance one adopts, this study does not aim to debate which views are more valid. Instead, it identifies a gap in the existing literature on marketing from an Islamic perspective: the lack of in-depth exploration of the term "marketing" within the Islamic jurisprudential heritage. It highlights the verbal and contextual connotations the term carries, which influence the formulation of many concepts and deduction of legal guidelines for marketing practices. In the absence of this crucial aspect, existing literature on marketing from an Islamic perspective often merely discusses the ethical dimensions of marketing practices, such as honesty, trustworthiness, avoidance of fraud, and deception. These aspects are not disputed, but often overshadowed by the broader, foundational principles of marketing within an Islamic framework. Marketing, being a mediation process aimed at achieving a fair sales deal, has its unique set of rules that align with the required practices and activities. The research concludes with an examination of the contextual significance of the term "marketing" and its legal texts, framing the fundamental marketing concepts. It indicates the concept, importance, purpose, requirements, cause, and Sharia rulings applicable to marketing, deducing legal guidelines for marketing mix elements. These can serve as a basis for determining the legitimacy of marketing practices.